Fenomena Gentrifikasi Planetari Kapitalisme Global: Dampak Sosial, Ekonomi, dan Eksklusi Ruang Perkotaan di Daerah Khusus Jakarta (DKJ) - Rizky Harnanto; Afifathu Rahmah Fajriyah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
The phenomenon of gentrification in big cities like Jakarta cannot be understood simply as a local process, but part of the dynamics of global capitalism that reconstructs urban spaces. This article examines how the logic of global capital accumulation and investment, particularly in the property and infrastructure sectors, drives spatial transformation and social marginalization in Jakarta. Using an urban political economy approach and a secondary literature review, the discussion shows that gentrification in Jakarta is characterized by rising land prices, changes in land ownership patterns, and forced relocation of low-income communities—especially the Betawi community. This process leads to the exclusion of space, where access to housing, public services, and urban space is increasingly concentrated in the upper-middle class and investors. A comparison with the city of Seoul shows that although gentrification also occurs in developed countries, the exclusion mechanism in developing countries is sharper due to weak regulations and dependence on foreign capital. This article recommends an integrated and inclusive approach to urban development, placing the right to the city as a fundamental principle for reducing social inequality and maintaining the sustainability of local culture.